Abstract 246: Effect of platelet count on outcome in ischemic stroke patients with LVO undergoing MT;a meta‐analysis - Muhammad Tayyab Muzaffar; Ahmad; Mishal; Hafiz Mohammad Maaz; Atrooba Zahid; Haris Kamal; Muhammad K Ahmed (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Large randomized clinical trials have established the superiority of Mechanical Thrombectomy (MT) for the treatment of Large Vessel occlusion (LVO) in patients with Acute Ischemic stroke (AIS) in terms of revascularization rates and clinical outcomes as compared to IV‐tPA alone.(1, 2, 3) However, Data regarding outcomes of mechanical thrombectomy in patients with low platelets is limited and shows conflicting results. (4, 5, 6, 7, 8) Methods This meta‐analysis was performed according to the preferred reporting items for systematic review and meta‐analysis (PRISMA) guidelines.(9) We defined thrombocytopenia as platelet count < 150,000 /μL. We further classified these patients into two groups: 1) Mild thrombocytopenia (Platelet count 100,000 – 149,000 /μL) and 2) Moderate to severe thrombocytopenia (Platelet count <100,000 /μL). The favourable outcome was 90‐day functional independence, designated as an Modified Rankin Score (MRS) ≤ 2 at 90 days. Unfavorable outcomes were 1) Symptomatic Intracranial hemorrhage (sICH) and 2) Mortality at 90 days. Results All studies were determined to be of good/high quality (Newcastle Ottawa scale).(10) Compared to patients with normal platelets, Patients with low platelets (< 150,000 /μL) had a statistically significant worse outcome (mRS >2 )at 90 days (RR 0.80 [95% CI: 0.69 ‐ 0.94] p = 0.006). However, on analysis based on different platelet cutoff values, the difference in mRS score was not statistically significant in patients with Mild low platelets (100,000 – 149,000 /μL) (RR 0.84 [95% CI: 0.70 ‐ 1.00] p = 0.05) and moderate/severely low platelets (< 100,000 /μL) (RR 0.71 [95% CI: 0.48 ‐ 1.06] p = 0.09) when compared to patients with normal platelets. Similarly, Mortality was significantly increased in patients in the low platelet group (RR 1.95 [95% CI: 1.62 ‐ 2.36] p < 0.00001). Mortality was also significantly increased in the mild low platelet subgroup (RR 1.88 [ 95% CI: 1.34 ‐ 2.63] p = 0.0002) and moderate/severe low platelet subgroup (RR 2.07 [95% CI: 1.46 ‐ 2.92] p < 0.0001) when compared to patients with normal platelets. Furthermore, sICH events were significantly increased in patients in the low platelet group (RR 2.47 [95% CI: 1.51 ‐ 4.05] p = 0.0003). Similarly, on analysis based on different platelet cutoff values, sICH was also significantly increased in the mild low platelet subgroup (RR 2.34 [ 95% CI: 1.24 ‐ 4.40] p = 0.008) and moderate/severe low platelet subgroup (RR 4.13 [95% CI: 2.00 ‐ 8.50] p = 0.0001). Conclusion Our meta‐analysis revealed that compared to individuals with normal platelet count, those with platelet count (< 150,000 /μL) had worse functional outcomes (MRS ≤ 2) , higher mortality rates, and a greater incidence of sICH. However, on analysis based on different platelet cutoffs, difference in MRS score was insignificant while the mortality rates and sICH incidence remained significantly higher. This may be attributed to smaller number of studies in the “cut‐off” groups leading to decreased power. Nevertheless, our findings suggest that MT for LVO in patients with low platelets leads to worse outcomes, however these risk were not significant in group with mild thrombocytopenia. Hence, Clinicians should carefully monitor for these risks while performing procedure or post procedure care.